SEPAKBOLA SEBAGAI MEDIA SOLIDARITAS POLITIK BAGI SUPPORTER INDONESIA - Perdana, Kiki Esa (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2018)
So far football has not only functioned as a sport but also as a medium of solidarity for supporters, Indonesia is a country with the largest Islamic religion in the world. While many other Islamic countries are still struggling with the problem of war, football believe, its is able to be a medium a solidarity. Message for the victims of war, prayers and solidarity messages are sent through. This research uses descriptive analysis with case studies of Rohingya and Palestinian cases in Indonesian football supporter. This research concludes that the message conveyed by Indonesian supporters. The conclusion, football is possible in becoming tools for political solidarity